2014
DOI: 10.1111/ggi.12140
|View full text |Cite
|
Sign up to set email alerts
|

Elevated inflammatory markers in diabetes‐related dementia

Abstract: (29%) were male. A total of 208 participants completed the questionnaire, of which 132 (63.5%) are aged less that 65 years and 76 (36.5%) where aged 65 years or older. No significant differences were found between age groups, level of education, family history of dementia and immigration status. Both sexes performed poorly on question 1 (females 24%; males 22%, χ 2 = 0.95, P = 0.759). However, in question 2, both sexes recognized symptoms of dementia (females 64%; males 75%, χ 2 = 2.27, P = 0.132). Albeit in q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The nervous system might be particularly vulnerable to glycemic variability . Our previous study showed that inflammatory cytokines and oxidative stress are associated with development of dementia and progression of cognitive decline in patients with DrD, but not in those with AD[+DM] . The present findings suggest that glucose variability is also associated with cognitive impairment in DrD.…”
Section: Discussionsupporting
confidence: 47%
“…The nervous system might be particularly vulnerable to glycemic variability . Our previous study showed that inflammatory cytokines and oxidative stress are associated with development of dementia and progression of cognitive decline in patients with DrD, but not in those with AD[+DM] . The present findings suggest that glucose variability is also associated with cognitive impairment in DrD.…”
Section: Discussionsupporting
confidence: 47%
“…In our previous study, we found that inflammatory markers, such as interleukin-6, were significantly higher in the DrD group than in the AD+DM group, and correlated with cognitive performance in the DrD group, indicating a possible role for inflammatory markers in cognitive impairment. 27 Our findings suggest that oxidative stress is also an important factor that might be involved in the pathophysiology of this dementia subgroup.…”
Section: Discussionmentioning
confidence: 63%
“…In our previous studies, patients with DrD showed significantly higher peripheral inflammatory and oxidative stress markers than those with AD − DM or AD + DM. 8,9 Although the exact inflammatory and oxidative mechanisms that contribute to frailty remain unclear, increased inflammation and high oxidative stress are involved in the pathophysiology associated with frailty in patients with DrD. Frailty is associated with a greater risk for adverse health outcomes including falls, disability, institutionalization and death.…”
mentioning
confidence: 99%